Associations of papaya leaf curl virus and betasatellite with yellow vein disease of pot marigold (Calendula officinalis L.). (14th December 2019) - Venkataravanappa, V.; Sonavane, Priti; Reddy, C. N. Lakshminarayana; Reddy, M. Krishna
Abstract: The calendula plants showing the yellow vein disease symptoms were collected from Madikeri dist. of Karnataka state, India. Total nucleic acid isolated from the infected Calendula plant leaf samples were subjected to PCR using begomovirus specific primer. The PCR diagnostic and whole genome sequencing indicated that the symptomatic calendula plants are associated with Papaya leaf curl virus (PaLCuV). The viral complete genome causing yellow vein disease had showed maximum nucleotide (nt) identity of 91.5–94.9% with begomovirus (PaLCuV) strains previously identified begomovirus from India infecting Croton bonplandianum, Acalypha sp. and chilli. Regarding to begomoviruses criteria for strain demarcation (91% nucleotide similarity), the virus infecting calendula in this report is considered as a strain of PaLCuV. The betasatellite showed maximum nucleotide identity of 89.8% with croton yellow vein mosaic betasatellite (CroYVMB) infecting okra and Croton . According to our knowledge, this is the first report of PaLCuV infecting the Calendula, in India. The result also indicated that calendula plants infected with PaLCuV may act as an alternate host for other economically important plant pathogens. Graphical Abstract: